(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The integration of business analytics, project management, and product management is revolutionizing the healthcare sector by driving innovation, advancing clinical outcomes, and streamlining operational processes. This study investigates how these three domains function collectively within healthcare organizations, highlighting their unified role in fostering data-informed decision-making, enhancing technological adoption, and delivering patient-focused solutions. Each discipline is defined within a healthcare-specific framework, and their interconnectedness is explored in relation to strategic implementation. The paper also outlines practical models for integration and includes case studies to demonstrate real-world applications. It addresses key obstacles such as fragmented data systems, compliance challenges, and institutional inertia, while offering actionable solutions and strategic practices to address them. In addition, emerging developments—such as the expanded use of AI and the evolution of hybrid roles in health technology—are examined. The paper ultimately offers a forward-looking strategy for healthcare leaders aiming to harness cross-functional management in a rapidly digitizing and patient-centered landscape.